Social Justice, the Graph of Zorro and the Outsider - Tanner, Adrian (Anthropologica, 2014)
This article surveys, from a social justice perspec tive, the author's experience of 50 years of field-based research in northern Indigenous communities, before and after that research involved local partnerships. While the objectivity of research is never absolute, it is a better guide to social justice than is political ideology. Examples are cited where public policy and certain politically influential academic research, are motivated by ideology, ignoring ethnographically based re sults. Finally an example from an unrelated context cites a study that showed, in the United States, that political affiliation determines either belief in or denial of anthropogenic climate change, regardless of educational level.